Evaluation of three-year work of pharmacist consultant in Murska Sobota Health Center - Kovačič, Alenka (Anali PAZU, 2022)
We evaluated work of clinical pharmacist consultant in the Community Health Center Murska Sobota from January 2013 to December 2015. In total 495 patients were reviewed. 3500 interventions and 2164 advices from pharmacist consultant were recommended. Furthermore, 159 potential drug-drug interactions type X and 947 interactions type D were identified. In recommendations only 19 type X and 232 type D potential drug-drug interactions were left. Other recommendations included 790 medicines discontinuations, 780 therapy replacements and 210 newly introduced medicines or OTC preparations. Mean number of prescribed medicines was reduced by 1.2 medicines per patient.
Keywords: pharmacist consultant practice; medication review; polypharmacotherapy